Lucas' expectational equilibrium, price rigidity, and descriptive realism - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2021)
Robert Lucas' 1972 article on the neutrality of money represented the first effective challenge to Samuelson's neoclassical synthesis methodological separation between static microeconomic optimization and macroeconomic dynamics. Lucas rejected disequilibrium price dynamics, as expressed by the Walrasian tâtonnement and auctioneer mechanisms. Lucas' new treatment of equilibrium as an expectational concept, determined by the rational behaviour of information processing agents, was not restricted to market clearing competitive economies. Lucas' effort to compare alternative rational expectations models of price stickiness (including his 1972 original formulation) led him to stress the notion of 'descriptive realism' of the models' main assumptions, which played an important role in his original discussion of model robustness.
Keywords: B22; B41; E32; 330; Robert Lucas; economic dynamics; expectational equilibrium; price rigidity; descriptive realism